VARIATIONS IN THE YIELD OF COCONUTS, AS INFLUENCED BY THE PATTERN OF RAINFALL AND DURATION OF DRYSPELL - Jacob Mathew; Amarnath C.H.; Vijaya Kumar K; Mohamed Yusuf; Balakrishnan T K. (International Coconut Community Journal, 1988)
Study of the variations in the yield of coconuts in the West Coast of India, in relation to the pattern of rainfall and duration of dryspell revealed that the yield obtained in any year is not directly related with the total rainfall received in the same year or in the preceeding years. Summer rains were having positive correlation with the yield in the succeeding year. About 60% of the variations in the annual yield were due to the changes in the duration of dryspell in the preceeding two years.